Karakterisasi Serat Pangan, Kapasitas Pengikatan Air dan Kemampuan Emulsifikasi Biji Selasih dan Chia - Dede Robiatul Adawiyah; Felia Prima Wefiani; Kezia Patricia (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2022)
Selasih (Ocimum basilicum) and chia seed (Salvia hispanica L.) are plant-based sources that have a unique characteristic of being able to form a gel when hydrated because they have a poly-saccharide layer that can bind water. The purpose of this study was to characterize selasih seed, Indo-nesian indigenous basil seed, compared to chia seeds which have been widely studied. The characteri-zation leads to functional properties for health and their potential to be applied to food products including crude fiber content, water holding capacity (WHC), and emulsification ability. The value of total dietary fiber which was quite high in both seeds (48.78 to 54.07%) had potential as a source of healthy dietary fiber. The selasih seed has water holding capacity and emulsion capacity that not significantly different from chia seed. The emulsification ability of selasih seeds and chia seeds needs proving by being applied to processed food products such as bakery products and processed meat products (sausages).